2010
DOI: 10.1007/s10265-010-0309-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic inheritance in green algae: patterns, mechanisms and relation to sex type

Abstract: Cytological and genetic investigations of two major groups of green algae, chlorophyte and streptophyte green algae, show a predominance of uniparental inheritance of the plastid and mitochondrial genomes in most species. However, in some crosses of isogamous species of Ulva compressa, these genomes are transmitted from mt+, mt(-), and both parents. In species with uniparental organelle inheritance, various mechanisms can eliminate organelles and their DNA during male gametogenesis or after fertilization. Conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 81 publications
0
24
0
Order By: Relevance
“…Although UPI is common, the mode (UPI male or mating type "minus" [mt − ], UPI female or mating type "plus" [mt + ], or BPI) can vary greatly among strains of green (chlorophytic) algal species (Miyamura 2010). For example, in the isogamous Ulva compressa, plastid DNA (ptDNA) inheritance can be UPI mt − , UPI mt + , or BPI, depending on the strains crossed, and mitochondrial DNA (mtDNA) inheritance is similarly variable.…”
Section: The Mode Of Inheritance For Mitochondria and Chloroplastsmentioning
confidence: 99%
“…Although UPI is common, the mode (UPI male or mating type "minus" [mt − ], UPI female or mating type "plus" [mt + ], or BPI) can vary greatly among strains of green (chlorophytic) algal species (Miyamura 2010). For example, in the isogamous Ulva compressa, plastid DNA (ptDNA) inheritance can be UPI mt − , UPI mt + , or BPI, depending on the strains crossed, and mitochondrial DNA (mtDNA) inheritance is similarly variable.…”
Section: The Mode Of Inheritance For Mitochondria and Chloroplastsmentioning
confidence: 99%
“…Since, the mode of organelle inheritance has been investigated in many groups (fig. 1); within the Chlorophyta, uniparental inheritance of both mtDNA and cpDNA has been reported in the Ulvophyceae, Chlorophyceae, and the Nephroselmidophyceae (Miyamura 2010). Uniparental inheritance of cpDNA has also been reported in the Trebouxiophyceae (Miyamura 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1); within the Chlorophyta, uniparental inheritance of both mtDNA and cpDNA has been reported in the Ulvophyceae, Chlorophyceae, and the Nephroselmidophyceae (Miyamura 2010). Uniparental inheritance of cpDNA has also been reported in the Trebouxiophyceae (Miyamura 2010). Within the Streptophytes, extensive literature exists for land plants and converges to the overall conclusion that their organelles are mainly maternally transmitted with the exception of the cpDNA that is mainly paternally transmitted in the Gymnosperms (Birky 1995).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we used the inheritance pattern of chloroplast DNA (cp-DNA) as a mating type specific marker because cp-DNA is generally transmitted to the offspring from one of the two mating types in green algae (Miyamura 2010). For A. caliculus, Kuroiwa et al (1985) already reported that cp-DNA derived from one of the two parents disappears after gamete fusion, suggesting that cp-DNA transmits to the next generation from one of the two mating types in the same way as C. reinhardtii (Kuroiwa et al 1982).…”
Section: Resultsmentioning
confidence: 99%